Pelayanan Jasa Keagenan Pengurusan Endorsement Dokumen Kapal dalam Rangka Kelancaran Berlayar - Suwandi, Suwandi; Rustina, Evada; Sumarwanto, Sumarwanto; Sri Sayekti Lestari; Rafdy Kaukabun Nufus (MAMEN: Jurnal Manajemen, 2023)
Agency services in handling ship document endorsements play an important role in ensuring that ships can operate properly and meet the requirements of applicable laws and regulations. Ship agents help manage this paperwork process efficiently, improving vessel smoothness and safety. The purpose of this study is to find out the procedures for clearance in and out services at shipping agents, know the process of handling ship document endorsements and also know the obstacles when handling ship documents that are no longer valid. This research was conducted at PT. Riandy Fiesta Ocean. This type of research is qualitative research with descriptive methods. Data collection techniques in this study use 4 data collection methods including: interviews, observations, documentation and literature studies. The result of this study is the procedure for clearence in and out services at shipping agents PT. Riandy Fiesta Samudera is required to be done appropriately and well, the ship document endorsement process requires good coordination and cooperation between agencies, port authorities, and other related agencies. Effective communication and timely exchange of information are essential to ensure the process runs smoothly. A deep understanding of regulations and requirements related to ship document endorsement is required by agency agencies. The process of handling ship document endorsements can be hampered if there is no quick response to requests or questions, or if there is a delay in completing documents.